Charactering the spoilage mechanism of “three sticks” of Jinhua ham - Changyu Zhou; Guang Zhan; Daodong Pan; Guanghong Zhou; Ying Wang; Jun He; Jinxuan Cao (Food Science and Human Wellness)
To investigate the spoilage characteristics of Jinhua ham, sensory scores, volatile compounds, biogenic amine, physicochemical parameters and microbial counts were evaluated between normal and spoiled hams. The results showed that off-odors of spoiled hams were dominated by rancid, sour, sulfide and ammonia odors derived from these compounds including butanoic acid, methanethiol and dimethyl disulfide. Total content of biogenic amine in spoiled hams was significantly higher (more than 10-fold) compared with normal hams, and putrescine, cadaverine and histamine were the key components of biogenic amine of spoiled hams. Lower salt content, and higher moisture, TVB-N and thiobarbituric acid reactive substances (TBARS) values were observed in spoiled hams compared with normal hams. The populations of Enterobacteriaceae and Enterococcus of spoiled hams were obviously higher than that of normal hams. High moisture and low salt content caused the abnormal growth of Enterobacteriaceae and Enterococcus in spoiled hams, which contributed to the spoilage of Jinhua ham.